2012
DOI: 10.1002/open.201200015
|View full text |Cite
|
Sign up to set email alerts
|

Direct Catalytic Asymmetric Synthesis of Pyrazolidine Derivatives

Abstract: Simple yet effective: A highly enantioselective, metal-free cascade reaction between di-1,2-N-protected hydrazine and α,β-unsaturated aldehydes is disclosed. The catalytic, asymmetric cascade transformation is a direct entry to 3-hydroxypyrazolidine and 3-allylpyrazolidine derivatives in one step and two steps, respectively, with >19:1 d.r. and 98–99 % ee using simple chiral pyrrolidines as catalysts

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 79 publications
(23 reference statements)
0
5
0
Order By: Relevance
“…Cordova and co‐workers also reported a similar asymmetric domino aza‐Michael/hemiaminalization reaction for the synthesis chiral pyrazolidine derivatives 53 (Scheme ) …”
Section: Primary and Secondary Amine Catalystsmentioning
confidence: 93%
See 1 more Smart Citation
“…Cordova and co‐workers also reported a similar asymmetric domino aza‐Michael/hemiaminalization reaction for the synthesis chiral pyrazolidine derivatives 53 (Scheme ) …”
Section: Primary and Secondary Amine Catalystsmentioning
confidence: 93%
“…[45] Cordova andc o-workers also reported as imilar asymmetric domino aza-Michael/hemiaminalization reactionf or the synthesis chiral pyrazolidine derivatives 53 (Scheme15). [46] Very recently,C hen and co-workers utilized 1,2-diaza-1,3-dienes 55 and b-substituted 2-butenals 56 as the reactionp artners in ad omino asymmetric vinylogous 1,6-Michaela ddition/1,4-proton shift/aza-Michael addition/hemiaminal formationr eaction (Scheme 16). [47] Thed ienamine catalysis using the chiral prolinol O-triphenylsilyl ether( S)-59 as the catalyst and 3,5-difluoromandelic acid (60)a sa na cid additive (the same stereoselectivity waso btained with both chiral andr acemic 60)p rovided the bicyclic l,8-diazabicyclo[3.3.0]octane skeletons 58 in high stereo-, regio-andchemoselectivities.…”
Section: 211synthesis Of Aza-heterocyclesmentioning
confidence: 99%
“…Pyrazolines and pyrazolidines both represent intermediates in the synthesis of pyrazoles and important building blocks for the diversification of in‐demand pharmaceutically active compounds . One facile routes pyrazolines is the 1,3‐dipolar cycloaddition of diazoalkanes with various dipolarophiles.…”
Section: Pyrazoles Pyrazolines and Pyrazolidinesmentioning
confidence: 99%
“…Shortly thereafter, Córdova and co‐workers carried out the reaction shown in Scheme , but with the participation of β‐arylsubstituted enals . This one‐step reaction (11 examples) proceeded in 98–99 % ee and 45–77 % yields.…”
Section: Pyrazoles Pyrazolines and Pyrazolidinesmentioning
confidence: 99%
“…[ 1–13 ] Therefore, many experimental and theoretical works have been dedicated to the efficient and stereoselective synthesis of pyrazolidine and pyrazoline compounds. [ 14–28 ] For instance, Kobayashi found that the Lewis acid chiral zirconium/BINOL complex can be used as an efficient catalyst to synthesize entioselectively pyrazolidine products via inter‐ or intra‐molecular [3+2] cycloaddition between hydrazones and alkenes. [ 22–24 ] Müller and List, however, used a chiral Brønsted acid to generate enantiopure pyrazolidine derivative.…”
Section: Introductionmentioning
confidence: 99%